2016
DOI: 10.1017/edp.2016.7
|View full text |Cite
|
Sign up to set email alerts
|

Involvement in Extracurricular Activities: Identifying Differences in Perceptions of School Climate

Abstract: Many youth participate in extracurricular activities, and research has linked activity participation with school engagement and academic success. Social-ecological theory suggests that the social contexts of different types of extracurricular activities may differentially affect student outcomes. Yet, there is scant research examining the relation between various extracurricular activities and student outcomes. The current study seeks to address this gap by exploring how participation in three activities (spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…Study shows that in involving oneself in extracurricular activities (ECA) may somehow be important in fostering school connectedness, hence the findings show that participation in ECA is associated with greater attachment in school than not participating in these activities [4]. Extracurricular activity participants had better grades, higher selfconcept, and educational attainment.…”
Section: Extra-curricular Activitiesmentioning
confidence: 89%
See 1 more Smart Citation
“…Study shows that in involving oneself in extracurricular activities (ECA) may somehow be important in fostering school connectedness, hence the findings show that participation in ECA is associated with greater attachment in school than not participating in these activities [4]. Extracurricular activity participants had better grades, higher selfconcept, and educational attainment.…”
Section: Extra-curricular Activitiesmentioning
confidence: 89%
“…The researchers have observed that in pageantry events, selective learning is evident among the students, they tend to be not participative most of the time and pay attention only to what catches their interest. Study shows that involving oneself in extracurricular activities (ECA) may somehow be important in fostering school connectedness, hence the findings show that participation in ECA is associated with greater attachment with the school than not participating in these activities [4]. Extracurricular activity participants had better grades, higher selfconcept, and educational attainment.…”
Section: Presentation Analysis and Interpretation Of Datamentioning
confidence: 89%
“…Participation in school-based extracurricular activities or afterschool programs has been shown to foster a sense of school connectedness (Anderson-Butcher, 2010;Martinez et al, 2016;Thompson et al, 2006). Past research has shown an association between smoking and frequent participation in extracurricular sport activities among off-reserve Indigenous youth (Ryan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Supervised, organized extracurricular activities have been associated with positive outcomes among youth, especially if these activities are structured in a manner that supports adolescents' developmental needs (e.g., forming caring relationships with adults and peers, engaging in identity exploration) (Fredricks & Eccles, 2008). It has also been suggested that different types of extracurricular activities (i.e., sport, art, or clubs) may provide students with qualitatively different developmental opportunities (Martinez et al, 2016). To this end, more research is needed to identify the features through which school-based club activities are associated with lower smoking prevalence among Métis high school students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation